2016
DOI: 10.1177/0148607115625779
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Aminotransferase/Platelet Ratio Index to Predict Liver Fibrosis in Intestinal Failure–Associated Liver Disease in Pediatric Patients

Abstract: APRI in this cohort of patients shows that a score >1.6 correlates with advanced fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…In children with biliary atresia, the APRI correlates with degree of fibrosis and predicts postoperative prognosis, but the cut‐points have varied between studies . Rumbo et al demonstrated that an APRI of ≥1.6 predicts advanced liver fibrosis in children with IFALD (sensitivity of 81% and specificity of 76%). In children with hepatocellular and biliary cholestasis, the cut‐points of APRI for discriminating advanced fibrosis were 0.93 (AUC, 0.68) in the hepatocellular group and 2.35 (AUC, 0.81) in the biliary group .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In children with biliary atresia, the APRI correlates with degree of fibrosis and predicts postoperative prognosis, but the cut‐points have varied between studies . Rumbo et al demonstrated that an APRI of ≥1.6 predicts advanced liver fibrosis in children with IFALD (sensitivity of 81% and specificity of 76%). In children with hepatocellular and biliary cholestasis, the cut‐points of APRI for discriminating advanced fibrosis were 0.93 (AUC, 0.68) in the hepatocellular group and 2.35 (AUC, 0.81) in the biliary group .…”
Section: Discussionmentioning
confidence: 99%
“…ALT is predominantly expressed in hepatocytes and is associated with the severity of liver disease . The reference value of ALT often quoted for infants aged <12 months is 3–35 IU/L .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alpha‐fetoprotein is suggested annually in patients with cirrhosis and ammonia in end‐stage IFALD. The aspartate aminotransferase‐to‐platelet index has not been helpful in predicting the degree of fibrosis in children with IFALD but may be useful in predicting cirrhosis …”
Section: Monitoring Of Long‐term Complicationsmentioning
confidence: 99%